Study the effect of elastic materials as interface medium used in infilled frames. (2018) - Muthu Kumar, S.; Satyanarayanan, K.S.
Abstract: The reinforced concrete (RC) Structural frames with masonry infill walls are widely used in buildings. The elastic connection between infill walls and RC frames is recommended in order to reduce the unfavorable interaction between them. In this study, two-bay and three-storeyed RC bare structural frame, RC infill frame with Cement mortar of rigid interface and RC infill frame with different interface having various flexible elastic combinations are analyzed. The influence of constructional details of infill walls on the seismic behavior of RC Structural frames is analyzed. Literature survey carried out in this area indicates that not much work has been done in studying the influence of interface material's elastic properties on the behavior of structural infilled frame. This study becomes now all the more significant as the recent trend is to use insulation material instead of common rigid elastic cement mortar at the interface. The objective of this research work is to study the influence of different interface materials with elastic property on the behavior of structural infilled frames. The scope of the work covers the elastic behavior of reinforced concrete frame with brick masonry infill with three different elastic interface materials, namely the commonly used cement mortar, cork and Rubber Foam. The objective is achieved by both numerical and experimental studies. It is found that with the addition of masonry infill wall rigidly connected to the frame, the lateral strength, and the stiffness of the bare RC frame increase significantly. Compared with the infill wall with rigid elastic connection, the strength, the stiffness and the energy-dissipation capacity contributed by the infill wall with flexible elastic connection drop significantly, but the displacement of the structures rises up.